PENGARUH NON PERFORMING LOAN DAN LOAN TO DEPOSIT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Alya Putri; Emillia Nurdin; Andi Muhammad Fuad Ramadhan Basru (Accounting Student Series on Emerging Trends, 2026)
This  study  aims  to  analyze  the  effect  of  Non-Performing  Loan  (NPL) and Loan to Deposit Ratio (LDR) on stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Stock prices  are  viewed  as  a  reflection  of  investors’  perceptions  of  company performance and risk; therefore, financial ratios that represent asset quality and  bank  liquidity  become  important  information  in  investment  decision- making. This study employs a quantitative approach using secondary data in the form of annual financial statements and stock prices on the publication date of the annual reports. The research sample consists of 19 banking companies with  a  total  of  57  observations,  selected  using  purposive  sampling.  Data analysis  is  conducted  using  panel  data  regression,  with  the  best  estimation model  determined  through  the  Chow  test,  Hausman  test,  and  Lagrange Multiplier test, resulting in the Random Effect Model as the most appropriate estimation model. The results indicate that, Non-Performing Loan (NPL) has a  negative  effect  on  stock  prices,  suggesting  that  an  increase  in  credit  risk reduces investor confidence. Meanwhile, Loan to Deposit Ratio (LDR) has no effect on stock prices, indicating that bank liquidity levels are not necessarily a  primary  consideration  for  investors  in  evaluating  banking  stocks  These findings support signaling theory, in which information related to credit risk is more strongly responded to by the market than liquidity indicators. This study is  expected  to  serve  as  a  reference  for  investors,  bank  management,  and regulators in understanding the factors influencing stock price movements in the banking sector.